Percepção de gestores e cidadãos sobre as cidades inteligentes: um estudo de caso em um município brasileiro de pequeno porte - Silva, Shariane Seleprin da (2023)
Currently, it is easy to find in the media mentions of innovative public management projects that make use of information and communication technologies in the most diverse areas, as well as awards and rankings that give cities the "label" of intelligence. However, it is not known to what extent this is perceived and recognized by society as a whole, especially by the inhabitants of these municipalities. From this perspective, the research aims to understand how the concept of "smart" and the aspects related to a smart city are perceived by the managers and citizens of a small Brazilian municipality, with the municipality of Madre de Deus (BA) being chosen. Data collection took place in two stages: qualitative, involving six interviews with managers involved in the development of smart projects and actions in the chosen municipality, and documentary research, analyzing the main strategic documents for the city's development linked to smart initiatives and projects; and quantitative, with a survey of the citizens of the chosen municipality. In the qualitative stage, we opted for a structured interview comprising 20 questions divided into three blocks. For the quantitative stage, a structured questionnaire was used with 31 questions, divided into two parts. For the first, 19 questions related to the perception of the concept of Smart City and its associations, as well as the perception and expectations of citizens regarding specific areas of action/technological solutions in the municipality of Madre de Deus, the studies by Cunha et al. (2016) and Santos (2019) were used as a research basis. The second part contained questions about citizens socio-economic data, knowledge of smart initiatives and projects, and citizen participation in Madre de Deus. This structure was validated by experts before being applied. The data analysis procedure involved three stages: in the qualitative part, content analysis was carried out; in the quantitative part, descriptive analysis was carried out and, finally, data triangulation. As for the concept, the results indicate that there is a divergence between the visions, while the managers' seem to be more aligned with the holistic approach, the citizens' responses are closer to the technocentric approach. There was also a divergence in the perception of citizens' interest in participating in definitions. While managers believe that there is little interest from citizens in participating, citizens indicate that they are interested, but do not participate because they are not aware of what is being developed. As for the expectations of the contributions of a smart city and the actions listed, the perceptions converge, as does the understanding that technology has a high impact on the quality of services provided in all dimensions, although there is already recognized by some of the managers that before discussing technological solutions, the most basic needs must be met. Although Madre de Deus has implemented projects in the different dimensions and built a path towards becoming a smart city, many of the strategic actions are not currently in operation or being used, including those recognized as important by citizens.